Adapting the Crohn’s disease exclusion diet to a Nordic framework: a theoretical approach to cultural and nutritional customization - Vivanco Karlsson, N.; Sigall-Boneh, R.; Mårild, K.; Hård Af Segerstad, E. M. (Frontiers in Nutrition, 2025)
Emerging evidence from diverse populations highlights the therapeutic benefits of the Crohn’s Disease Exclusion Diet (CDED) in managing Crohn’s Disease. To improve the efficacy of the CDED, there is a need to focus on cultural adaptation and individualization to support dietary adherence to this advanced nutritional therapy. This paper provides a theoretical framework for modifying the CDED to align with a Nordic diet (Nordic-CDED), while retaining the core principles and nutritional characteristics of the original protocol. Through a comprehensive literature review and expert consensus, we propose a Nordic-CDED that incorporates European regulations on food additives, the 2023 Nordic Nutritional Recommendations, and Nordic food culture. We present a theoretical foundation for an inclusion of whole foods and discuss the selection of enteral formulas. The adaptation also emphasizes the importance of dietitian-led guidance to tailor the Nordic-CDED to the patient’s age, lifestyle, and personal preferences. Further research is required to assess the clinical effectiveness and adherence to the Nordic-CDED.